Partial discharge signal measurement based on stand-alone and hybrid detection technique for power transformer - Jalil M.A.A.; Rosmi A.S.; Rohani M.N.K.H.; Isa M.; Auni W.N.; Abdullah A.Z.; Aizam M.T. (Institute of Advanced Scientific Research, Inc., 2023)
Partial discharge (PD) is a phenomenon that causes failures in high voltage (HV) components due to the degradation of insulation. Before an interruption or fault occurs, early detection of insulation degradation is essential. However, the long-term effect of PD will lead to the failure of the power system. This is important to control and diagnose the health of the HV power equipment such as power transformer. The main issue when measuring PD is the accuracy and sensitivity of the PD detection technique. This paper consists of two parts which are classification of the PD detection technique and hybrid detection technique. In this paper, an overview of the detection technique for power transformer including optical detection, chemical detection, electrical detection, electromagnetic detection, acoustic emission detection and hybrid detection technique is presented. The hybrid detection technique is based on combining two or more stand-alone detection technique. Based on this review, the hybrid detection technique showed that the advantages of performance in terms of sensitivity and accuracy for detecting the PD in power transformer. 2020, Institute of Advanced Scientific Research, Inc. All rights reserved.